Agglomeration and clustering over the industry life cycle: Toward a dynamic model of geographic concentration. (25th June 2013) - Wang, Liang; Madhok, Anoop; Xiao Li, Stan
<x xml:space="preserve">Abstract</x> Research on agglomeration finds that either a higher survival rate of incumbent firms or a higher founding rate of new entrants, or both, can sustain an industry cluster. The conditioning effects of time on the two distinct mechanisms of survival and founding are, however, rarely examined. We argue that the forces driving geographic concentration vary across the industry life cycle. Data from Ontario's winery industry from 1865 to 1974 demonstrates a dynamic model of geographic concentration: agglomeration attracts more new entry in the growth stage only, whereas it contributes to firm survival in the mature stage only. The results not only establish the importance of understanding the temporal dynamics underlying agglomeration externalities, but also provide a possible explanation for the mixed empirical results found in previous studies. Copyright © 2013 John Wiley & Sons, Ltd.